The TV showrunner's roadmap : creating great television in an on demand world - Landau, Neil (Routledge, 2022)
"This all-new edition of the best-selling guide The TV Showrunner's Roadmap provides readers with the tools for creating, writing, and managing your own hit streaming series. Combining his 30+ years as a working screenwriter and professor, industry veteran Neil Landau expertly unpacks essential insights to the creation of a successful show, and takes readers behind the scenes with exclusive and enlightening interviews with showrunners from some of TV's most lauded series, including Fargo, Better Call Saul, Watchmen, Insecure, Barry, Doctor Who, Succession, Ozark, Schitt's Creek, Euphoria, PEN15, and many more. From conception to final rewrite, The TV Showrunner's Roadmap is an invaluable resource for anyone seeking to create a series that won't run out of steam after the first few episodes. This groundbreaking guide features an eResource with additional interviews and bonus materials. So grab your laptop, dig out that stalled spec script, and buckle up. Welcome to the fast lane"--